2022
DOI: 10.3762/bjnano.13.115
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered docetaxel-loaded chitosan-decorated cationic PLGA nanoparticles for intestinal tumors: formulation, comprehensive in vitro characterization, and release kinetics

Abstract: Intestinal cancers are the third most lethal cancers globally, beginning as polyps in the intestine and spreading with a severe metastatic tendency. Chemotherapeutic drugs used in the treatment of intestinal tumors are usually formulated for parenteral administration due to poor solubility and bioavailability problems. Pharmaceutically, clinical failure due to a drug’s wide biodistribution and non-selective toxicity is one of the major challenges of chemotherapy. In addition, parenteral drug administration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…Unal et al determined that in uncoated NPs, zeta potentials ranged from − 20.1 to -25.8, whereas in coated NPs, surface charges ranged from + 29.6 to + 57. [12]. They demonstrated that the zeta potential of NPs coated with chitosan and PCL used in the study changed from negative to positive [12].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Unal et al determined that in uncoated NPs, zeta potentials ranged from − 20.1 to -25.8, whereas in coated NPs, surface charges ranged from + 29.6 to + 57. [12]. They demonstrated that the zeta potential of NPs coated with chitosan and PCL used in the study changed from negative to positive [12].…”
Section: Discussionmentioning
confidence: 91%
“…Due to the biodegradable and biocompatible features of PCL, it is frequently used in drug development studies as it facilitates drug release and long-term degradation up to several months [8]. In literature, have been found studies related with Paclitaxel [12], Quercetin [18], Irinotecan [19], 5-Fluorouracil [20] and Atorvastatin calcium [21] loaded PCL nanoparticle. In the literature, there are just only two studies on the nanoform of ruxolitinib: gold-coated nanoparticles of Ruxolitinib [17] and a topical emulgel containing Ruxolitinib nanoliposome [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations